Efficacy and safety of a readjustable midurethral sling (Remeex system) for stress urinary incontinence with female voiding dysfunction - Chung, Jae-Wook (Investig Clin Urol, 2017)
PURPOSE: We investigated the efficacy and safety of a readjustable midurethral sling (Remeex system) for stress urinary incontinence with female voiding dysfunction. MATERIALS AND METHODS: From May 2007 to December 2015, 151 women received the Remeex system. We excluded patients who presented with pelvic organ prolapse and/or who missed the regular follow-up. Finally, 102 patients were included in the study, and we divided them into 2 groups: group A (n=74), who did not present with female voiding dysfunction and group B (n=28), who presented with female voiding dysfunction. Female voiding dysfunction was defined as a maximal flow rate≤12 mL/s when the voided volume was ≥150 mL on preoperative uroflowmetry. We retrospectively reviewed the patients' medical records and compared surgical outcomes between groups A and B. RESULTS: There were no significant differences in subjective surgical outcomes and patient satisfaction between the 2 groups. Postoperative uroflowmetry showed that the maximal flow rate and voided volume decreased and the postvoid residual urine volume increased in both groups, and these changes were not significantly different between groups. The overall complication rate was 21.6% (22 of 102), and the complication rate was not significantly different between the 2 groups according to the modified Clavien-Dindo classification. CONCLUSIONS: The Remeex system is efficacious and safe for stress urinary incontinence with female voiding dysfunction.